Y=ln(ln(x))
y'=(1/x)/Ln(x)=1/xln(x)
Answer:
a bc I think it's right idk really
Step-by-step explanation:
jdlaifnshfjtjtjfjdjsjdurbxusnejskshduanwufnrudjdjfkgkgjdjfjgktjvinehdovndintivnsjvolebvinebfirbxjbwhgoenchbtijbegijrgcihegcinrhd
Answer:
0
Step-by-step explanation:
Write out the 2 equations:
2x + y = -3
-2y = 6+4x
-You then pick a variable that you want to solve for. I chose to solve for y because it would be a bit easier.
-2y = 6 + 4x
-Divide both sides by -2 to isolate the variable
(-2y) / -2 = (6 + 4x) / -2
-it comes out to y = -3 -2x
-Now that you have the y you can plug in the value into the second equation.
2x + y = -3 ---> 2x + (-3 -2x) = -3
This can be simplified to:
2x - 3 - 2x = -3
The 2x's cancel out because there is a +2x and a -2x. You are left with a
-3 = -3. If you add 3 to both sides of the equation you end up with 0 = 0, which can be simplified to just 0.
Answer:
x=7
Step-by-step explanation:
y=mx
5.5=m×11
5.5÷11=m
m=1/2
y=mx
3.5=1/2×x
3.5÷1/2=x
x=7